Válaszúton – rendiség, abszolutizmus, polgárosodás? Hatalomgyakorlási modellek Jean Bodin Az államról című könyvében - Szentgáli-Tóth, Boldizsár (Debreceni Jogi Műhely, 2013)
The article approaches Bodin’s philosophy from historical aspect outlining the characters of age of reformation. The paper emphasizes, Bodin’s work came into existence in a transitional time, wherein holy and profane views coexisted, often interspersed. The conception of Bodin reflects a relatively rational way of thinking introducing the state phenomena as parts of political power structure. The writing analyses the functions of state and their institutions and operation. The article introduces Bodin’s ideas about the professional state control and its relations with our modern public administration.